Nekaj poglavij iz zgodovine (kratkih) stikov (post)semiotične uprizoritvene teorije in prakse - Toporišič, Tomaž (Primerjalna književnost, 2016)
This article uses several examples of dramatic and performing practices and their possible theorizations to discuss the transformation of semiotic approaches to these two closely connected fields, from the 1960s performative shift to the present. It explores which representation and theorization strategies have proved fruitful.
Keywords: semiotics; semiotika; uprizoritvene umetnosti; postdramsko gledališče; dramski tekst; postdramski tekst; mediatizirane umetnosti; umetnosti v živo